2012
DOI: 10.1021/ac3006439
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping Botulinum Neurotoxins by Sequential Multiple Endoproteases In-Gel Digestion Coupled with Mass Spectrometry

Abstract: Botulinum neurotoxin (BoNT) is one of the most toxic substances known. BoNT is classified into seven distinct serotypes labeled A through G. Among individual serotypes, researchers have identified subtypes based on amino acid variability within a serotype and toxin variants with minor amino acid sequence differences within a subtype. BoNT subtype identification is valuable for tracing and tracking bacterial pathogens. A proteomics approach is useful for BoNT subtyping since botulism is caused by botulinum neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…For instance, the translocation domain of E10 is highly homologous to that found in all variants except E9 and E11, while large portions of its catalytic and receptor-binding domains are identical to those of E11. Such patterns suggest the occurrence of recombination events and have been previously reported for other bont genes, including bont/E variants, and toxin gene clusters (2,9,15,28). The frequency of nucleotide substitutions observed within variants E10 (1 to 7 nucleotides) and E3 (1 or 2 nucleotides) is similar to that reported for variant B4 (1 to 5 nucleotides), a toxin variant generally associated with nonproteolytic C. botulinum (29).…”
Section: Discussionsupporting
confidence: 83%
“…For instance, the translocation domain of E10 is highly homologous to that found in all variants except E9 and E11, while large portions of its catalytic and receptor-binding domains are identical to those of E11. Such patterns suggest the occurrence of recombination events and have been previously reported for other bont genes, including bont/E variants, and toxin gene clusters (2,9,15,28). The frequency of nucleotide substitutions observed within variants E10 (1 to 7 nucleotides) and E3 (1 or 2 nucleotides) is similar to that reported for variant B4 (1 to 5 nucleotides), a toxin variant generally associated with nonproteolytic C. botulinum (29).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, Endopep-MS detects active toxin down to serotype level. Also, it has been demonstrated that the subtype can be determined by a subsequent proteomics approach applied on the antibody captured toxin after the Endopep-MS procedure [22,26,40,41]. There are several successful examples of the use of Endopep-MS for the detection of BoNTs in different matrices [42,38].…”
Section: Introductionmentioning
confidence: 99%
“…Using antibodies to the toxin, the toxin has been isolated from food [4345] or bacterial culture [44, 46]. Through this process, both BoNT/A [4345] and BoNT/B [44, 46] were reported to be detected even in the presence of complex matrices. The sequence coverage on the neurotoxin using this process was reported as between 65 and 98%.…”
Section: Bont Serotype Detection In Complex Matricesmentioning
confidence: 99%
“…In 2012, Wang et al reported on a new technique to improve sequence coverage of BoNT proteins [45]. This work consisted of separation of the protein complex components by SDS-PAGE followed by digestion of each gel band with multiple enzymes and sequential in-gel digestion.…”
Section: Differentiation Of Bont At the Subtype/toxin Variant Levelmentioning
confidence: 99%
See 1 more Smart Citation